Case Report of Multimodality Imaging in Omental Cake: Plain Radiograph, Computed Tomography, and Ultrasonography. Issue 45 (November 2015) - Juan, Yu-Hsiang; Cheung, Yun-Chung; Ng, Koon-Kwan; Ng, Shu-Hang; Huang, Jen-Seng; Chang, Liang-Che; Lin, Yu-Ching
Abstract : Abstract: The imaging finding of omental cake has been demonstrated in other modalities, such as computed tomography, magnetic resonance imaging, and ultrasonography. However, to the best of our knowledge, the image presentation of omental cake on a routine kidney-ureter-bladder film has not been reported before in the literature. We presented a unique case of a 61-year-old woman, with known advanced cecal colon mucinous adenocarcinoma, presented to our institution with abdominal fullness, poor appetite, and decreased stool passage for 20 days. Physical examination was unremarkable, except distended abdomen. Subsequent study revealed massive post-pigtail catheter drainage ascites with a prominent soft-tissue mass-causing centralization and tethering of focally distended small bowel gas, suggestive of omental cake on plain radiograph. The imaging finding in plain radiograph corresponds to the findings in other imaging modalities, including abdominal sonography and computed tomography. The patient underwent subtotal colectomy and ileostomy during later courses of chemotherapy due to adhesion ileus and possible intraabdominal abscess, and pathologic study confirmed the diagnosis of cecal mucinous adenocarcinoma and peritoneal carcinomatosis. Although the image finding of omental cake on plain radiograph has never been described, this image finding is unique and should be recognized, as it may suggest the presence of omental cake when first identified in the emergency department from patients with abdominal distension and warrant further evaluation to evaluate the underlying cause.